Cystic Fibrosis Lung Disease: A Narrative Literature Review - Putra, Rizki Amrika; Masrul Basyar; Yessy Susanty Sabri (HM Publisher, 2024)
Cystic fibrosis (CF) is caused by mutations in autosomal recessive genes that code for proteins cystic fibrosis transmembrane conductance regulator (CFTR) which is located on chromosome seven. The CFTR protein under normal conditions acts as a chloride channel and helps the movement of sufficient electrolytes and water across the membrane. Mutations in CFTR cause abnormalities in chloride ion transport through epithelial cells and impaired sodium and water transport resulting in viscous secretions with low water content. This thick and sticky secretion will inhibit the normal function of various organs, although pulmonary complications are the most common cause of death. Cystic fibrosis has wide genotypic and phenotypic variations. There are six categories of mutations based on their effect on the CFTR protein, where these categories are not only used to predict the phenotype but also to determine better therapeutic strategies based on the identified mutations.